2015
DOI: 10.1016/j.cub.2015.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Microtubules Drive Circuit Rewiring in the Absence of Neurite Remodeling

Abstract: A striking neuronal connectivity change in C. elegans involves the coordinated elimination of existing synapses and formation of synapses at new locations, without altering neuronal morphology. Here, we investigate the tripartite interaction between dynamic microtubules (MTs), kinesin-1, and vesicular cargo during this synapse remodeling. We find that a reduction in the dynamic MT population in motor neuron axons, resulting from genetic interaction between loss of function in the conserved MAPKKK dlk-1 and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
81
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(83 citation statements)
references
References 45 publications
(72 reference statements)
2
81
0
Order By: Relevance
“…21 Much to our surprise, we found that while DD neurites switch polarity after synapse remodeling, with the ventral neurite assuming a dendritic and dorsal neurite an axonal identity, their MT polarity remained unchanged. 22 This observation shows that neurite identity could be uncoupled from MT polarity, and suggests that the specificity of axonal and dendritic cargo might be determined by factors besides the orientation of MTs.…”
Section: The Cellular Changes That Facilitate Dd Remodelingmentioning
confidence: 87%
See 4 more Smart Citations
“…21 Much to our surprise, we found that while DD neurites switch polarity after synapse remodeling, with the ventral neurite assuming a dendritic and dorsal neurite an axonal identity, their MT polarity remained unchanged. 22 This observation shows that neurite identity could be uncoupled from MT polarity, and suggests that the specificity of axonal and dendritic cargo might be determined by factors besides the orientation of MTs.…”
Section: The Cellular Changes That Facilitate Dd Remodelingmentioning
confidence: 87%
“…One possible factor regulating cargo trafficking is the number of dynamic MTs, as we observed a dramatic increase in dynamic MTs during DD remodeling. 22 Indeed, DD remodeling was dependent on this increase in growing MTs, such that mutant animals with fewer dynamic MTs during remodeling failed to rewire their synapses to the dorsal neurite. 22 The increase in number of dynamic MTs facilitates synaptic vesicle transport mediated by plus-end directed motors UNC-104/Kinesin-3 and UNC-116/Kinesin-1 22 along the DD neuron commissure during remodeling.…”
Section: The Cellular Changes That Facilitate Dd Remodelingmentioning
confidence: 99%
See 3 more Smart Citations